Diagnostic Approaches to Moyamoya Disease in a Patient with Head Trauma - Putri, Amanda; Kesuma Ningrum, Mutiara; Rachman Kemal, Mohammad Arief; Gunawan, Kevin (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2026)
Introduction: Moyamoya Disease (MMD) is a chronic cerebrovascular disorder characterized by progressive stenosis and occlusion of the distal internal carotid artery and the proximal segments of the middle and anterior cerebral arteries. This leads to the development of abnormal vascular networks at the base of the skull, resulting in a